ANALISIS KAUSALITAS INDEKS HARGA SAHAM GLOBAL DENGAN INDEKS HARGA SAHAM GABUNGAN - Fajri Rizky Arsyi, (2021)
The study aims to analyze whether the DJIA in the United States, the SSEC in China and the N225 in Japan influenced the movement of the JCI in Indonesia. Sample used in this research are monthly price data of DJIA, SSEC, N225 and JCI during the period January 2018 - December 2019. The data analysis method used is OLS with assistance of Eviews version 10 program and 5% significance level. The results of this study are (1) DJIA affects the movement of JCI in Indonesia, (2) SSEC affects the movement of JCI in Indonesia, (3) N225 affects the movement of JCI in Indonesia.